Proteotyping as alternate typing method to differentiate Campylobacter coli clades - Emele, Matthias Frederik (Sci Rep, 2019)
Besides Campylobacter jejuni, Campylobacter coli is the most common bacterial cause of gastroenteritis worldwide. C. coli is subdivided into three clades, which are associated with sample source. Clade 1 isolates are associated with acute diarrhea in humans whereas clade 2 and 3 isolates are more commonly obtained from environmental waters. The phylogenetic classification of an isolate is commonly done using laborious multilocus sequence typing (MLST). The aim of this study was to establish a proteotyping scheme using MALDI-TOF MS to offer an alternative to sequence-based methods. A total of 97 clade-representative C. coli isolates were analyzed by MALDI-TOF-based intact cell mass spectrometry (ICMS) and evaluated to establish a C. coli proteotyping scheme. MLST was used as reference method. Different isoforms of the detectable biomarkers, resulting in biomarker mass shifts, were associated with their amino acid sequences and included into the C. coli proteotyping scheme. In total, we identified 16 biomarkers to differentiate C. coli into the three clades and three additional sub-clades of clade 1. In this study, proteotyping has been successfully adapted to C. coli. The established C. coli clades and sub-clades can be discriminated using this method. Especially the clinically relevant clade 1 isolates can be differentiated clearly.